Broad spectral response photodetector based on individual tin-doped CdS nanowire - Weichang Zhou; Yuehua Peng; Yanling Yin; Yong Zhou; Yong Zhang; Dongsheng Tang (AIP Advances, 2014)
High purity and tin-doped 1D CdS micro/nano-structures were synthesized by a convenient thermal evaporation method. SEM, EDS, XRD and TEM were used to examine the morphology, composition, phase structure and crystallinity of as-prepared samples. Raman spectrum was used to confirm tin doped into CdS effectively. The effect of impurity on the photoresponse properties of photodetectors made from these as-prepared pure and tin-doped CdS micro/nano-structures under excitation of light with different wavelength was investigated. Various photoconductive parameters such as responsivity, external quantum efficiency, response time and stability were analyzed to evaluate the advantage of doped nanowires and the feasibility for photodetector application. Comparison with pure CdS nanobelt, the tin-doped CdS nanowires response to broader spectral range while keep the excellect photoconductive parameters. Both trapped state induced by tin impurity and optical whispering gallery mode microcavity effect in the doped CdS nanowires contribute to the broader spectral response. The micro-photoluminescence was used to confirm the whispering gallery mode effect and deep trapped state in the doped CdS nanowires.